La critique musicale au temps des encyclopédistes - Coronat-Faure, Raphaële (Paris Champion, 2001)
Featuring a wide range of texts, this book offers a study of the different parameters of music criticism in the mid-Enlightenment.Through a systematic examination of a number of sources (Mercure de France, L'Avant-Coureur, Mémoires secrets, Correspondance littéraire, as well as certain aesthetic writings), the author highlights the construction of musical reviews in the eighteenth century, the recurring elements of these chronicles and attempts to define the purpose of criticism at the time. A study of the editors' general and musical knowledge enables us to understand, and sometimes clarify, the position taken by these critics, and the style and vocabulary employed.Thanks to the emergence of aesthetic thinking, music criticism at this time took on its modern form. With the help of a few selected texts, this work shows the link between the musical 'soirées' proposed and the evolution of the interpretation of the classical idea on which thinkers still rely, namely the imitation of nature. Finally, even if journalistic criticism is essentially one of information and judgment, its historical value cannot be overlooked, thanks to the wealth of information and details it provides on a world that has disappeared, and of which it is one of the rare remaining witnesses today. (Translated with DeepL.com)
Keywords: 18th Century (1701-1800); Music history; Music criticism; Journalism; France